2003
DOI: 10.1021/es026262d
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Chlorine Speciation on de Novo Formation of Polychlorinated Dibenzo-p-dioxins and Polychlorinated Dibenzofurans

Abstract: The role of chlorine speciation on de novo formation of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDDs/Fs) has been studied thoroughly in an entrained flow reactor during simulated waste combustion. The effects of gas-phase chlorine species such as chlorine (Cl2), hydrogen chloride (HCl), and chlorine radicals (Cl*), as well as ash-bound chlorine, on PCDD/F de novo formation were isolated for investigation. The ash-bound chlorine alone was observed to be a sufficient chlorine source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 30 publications
(45 reference statements)
8
65
0
Order By: Relevance
“…The UP-POP concentrations were far lower in fly ash from the coking processes than from the waste incineration and metallurgical fly ash. The elemental compositions of the raw material and the fly ash are very important in the formation of UP-POPs [13,24], and the effect of chlorine and sulfur on PCDD/F formation has been investigated in many studies [25,26]. The ratio of sulfur to chlorine (R S/Cl ) normally correlates with the PCDD/F concentrations formed, with a low ratio indicating a high chlorine content, which can promote PCDD/F formation, and a low sulfur content, which inhibits PCDD/F formation.…”
Section: Concentrations Of Up-pops In Fly Ash Samplesmentioning
confidence: 99%
“…The UP-POP concentrations were far lower in fly ash from the coking processes than from the waste incineration and metallurgical fly ash. The elemental compositions of the raw material and the fly ash are very important in the formation of UP-POPs [13,24], and the effect of chlorine and sulfur on PCDD/F formation has been investigated in many studies [25,26]. The ratio of sulfur to chlorine (R S/Cl ) normally correlates with the PCDD/F concentrations formed, with a low ratio indicating a high chlorine content, which can promote PCDD/F formation, and a low sulfur content, which inhibits PCDD/F formation.…”
Section: Concentrations Of Up-pops In Fly Ash Samplesmentioning
confidence: 99%
“…Many sources for the emission of UP-POPs have been identified and quantified (7,8), and the effects of various parameters on the formation of UPPOPs have been demonstrated in many studies (9)(10)(11)(12)(13). Sources of POPs and their relative importance have changed substantially over the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…For CP3, the gas emitted from charging of the coal was conducted into the adjacent combustion chambers, which might result in very low emission level of the dioxins. It was reported that the composition of raw materials in thermally related processes had significant influence on dioxins formations and emissions (Tuppurainen et al, 1998;Hatanaka et al, 2000;Wikström and Marklund, 2001;Wikstörm et al, 2003;Wang et al, 2003;Zheng et al, 2004). Therefore, the contents and forms of some elements in coal used for coke production, such as chlorine, copper, and sulfur, are supposed to also affect dioxin emissions.…”
Section: Resultsmentioning
confidence: 99%